MAIN FACTORS AND CONDITIONS FOR DESIGNING CABINET KITCHEN FURNITURE - Абизов, В. А.; Булгакова, Т. В.; Агліуллін, Р. М. (Art and Design, 2023)
The aim of the study is to identify the main factors and conditions for designing cabinet kitchen furniture. Methodology. The analysis of literary sources on the design of furniture; structural and system analysis; synthesis of research results have been used in the study. Results. The design of kitchen furniture and equipment plays an important role in creating a comfortable living environment for the consumer. Designer taking into account the main factors and conditions for the creation of furniture of this type is the basis for creating high-quality furniture design and a comfortable living space. It has been determined that the creation of cabinet kitchen furniture should be based on the following groups of factors: socio-economic, ergonomic-spatial, functional-typological, ecological, constructive-technological and aesthetic, driven by the close interaction of these factors in the process of the design creation and phasing of the designer's work. In accordance with these groups of factors, the conditions for designing kitchen cabinet furniture have been defined. Considering the mentioned factors and the corresponding conditions for the creation of furniture of this type will provide an opportunity to determine the characteristics of a specific consumer, which is relevant within the human-oriented approach to design. The creation of kitchen cabinet furniture based on the specified conditions is a key requirement for successful furniture design and thus leads to a positive result – comfort of the consumer. Scientific novelty. For the first time, the factors and corresponding conditions for designing cabinet kitchen furniture, which are the basis of quality design of the living environment, have been determined. The practical significance of the obtained results lies in the possibility of their application for designers and manufacturers in the design of cabinet kitchen furniture.